The karyotype of Adenomera diptyx (Boettger 1885) (Anura, Leptodactylidae) from northeastern Argentina - Zaracho, Victor Hugo (2011)
In this work we analyzed the karyotype of five populations of Adenomera diptyx from Argentina after conventional staining, Ag-NOR and C-banding. All specimens presented 2n = 26 and FN = 34. The karyotype was formed by three submetacentric, one metacentric and nine telocentric pairs. Silver staining revealed that the NOR was located on a secondary constriction in pair 7. C- banding evidenced constitutive heterochromatin at the pericentromeric region of all chromosomes. The karyotype of A. diptyx was similar to that of A. hylaedactyla (2n = 26, FN = 34) and different from that of A. andreae (2n = 26, FN = 40) in the fundamental number and secondary constriction position. It also differed from the karyotypes of A. marmorata (2n = 24, FN = 34 and 36) and of A. aff. bokermanni (2n = 23, FN = 34) in diploid number. Until a comprehensive cytogenetic analysis of all the species of the genus is performed, their chromosome evolution will remain poorly understood.